LARANGAN KEPEMILIKAN TANAH SECARA LATIFUNDIA BERDASARKAN PASAL 7 UNDANG-UNDANG NOMOR 5 TAHUN 1960 TENTANG POKOK AGRARIA (UUPA) - Zubaedi, Zubaedi (Jurnal Muhakkamah, 2020)
Land is a very vital asset for humans who is given by God the Almighty, land is used as a place to live, a place to grow crops, a place to build various things and various other benefits so that people are competing to own it. Because land is so important to the community, it does not expect that many people own land in such a large number and on the other hand there are also many people who do not own a piece of land, this has created social inequality in the community even though the distribution of natural resource use must be evenly distributed among the people. all levels of society which is the mandate of the constitution. The problem in this writing is how is the implementation of article 7 of the UUPA concerning the prohibition of latifundia in the community and how the role of the government in this case is BPN to overcome land ownership by latifundia. The method used in this writing is the empirical normative method, which examines the laws and regulations or norms and concepts that apply and examines the implementation of these norms in society. The purpose of this paper is to provide an overview to the community about the concepts and prohibitions of latifundia land ownership and what are the impacts and consequences as well as to provide an overview of the duties and authorities of BPN in overcoming these problems so that people become aware and aware of the law and are more careful in transacting in the land sector. which in turn can create an even distribution of land and an even distribution of community welfare.